2017
DOI: 10.2147/amep.s131851
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of lecturing approaches: traditional versus interactive teaching

Abstract: BackgroundThere is an increasing trend toward transcending from traditional teaching to student-centered methodologies that actively engage students. We aimed to analyze students’ perceptions of effective interactive teaching using PollEverywhere Audience Response System (ARS) as a worthwhile teaching methodology. It can be of great help in maintaining students’ attention and in facilitating the lecturer to pick up students’ misunderstandings and correct them.Materials and methodsThis system was introduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 22 publications
6
44
1
3
Order By: Relevance
“…In conclusion, we agree with Abdel Meguid and Collins1 that when used effectively, ARS can have a significant role in higher education, and their study – together with our own experience in medical school – strongly supports this. While there are potential limitations to widespread ARS use in medical education, there is no reason why these cannot be overcome.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In conclusion, we agree with Abdel Meguid and Collins1 that when used effectively, ARS can have a significant role in higher education, and their study – together with our own experience in medical school – strongly supports this. While there are potential limitations to widespread ARS use in medical education, there is no reason why these cannot be overcome.…”
supporting
confidence: 86%
“…We agree with the importance of open-ended questions as mentioned in the Abdel Meguid and Collins1 article. For us, questions requiring critical thinking were much more beneficial than simple recall questions (although these also had value) and often sparked productive conversation surrounding the reasoning of responses.…”
supporting
confidence: 84%
“…Dissection was made more effective by introducing team‐based tasks to promote collaborative learning (Kang et al, ). Lectures were made effective by making them interactive, that helped in developing problem‐solving skills and communication skills (Steinert and Snell, ; Mazur, ; Wolff et al, ; Abdel Meguid and Collins, ). Although numerous interactive techniques are available for small‐group teaching, effective interactive techniques for large‐group teaching are scarce (Chan, ; Wolff et al, ; Abdel Meguid and Collins, ).…”
Section: Introductionmentioning
confidence: 99%
“…This way of teaching enables medical educators to assess students' progress, satisfaction and understanding to ensure that learning is achived. 9 However, many tutors report that students' performance is often not monitored or tested until the final summative exam. 10 Moreover, students state that a lack of formative feedback affects the teaching and learning process.…”
mentioning
confidence: 99%
“…This gives educators a powerful advantage, enabling intervention and support at an early stage of study. 9,10 ARS technology is used to promote active learning within the classroom in numerous disciplines. 8 Researchers have identified that ARS use in combination with question-driven instruction make classroom teaching more student-centred, creating an environment for active learning.…”
mentioning
confidence: 99%